Homosexualiteit - Overing, A.F.C.; Kempe, G.Th.; Vermeulen, Jos; Trimbos, C.J.B.J. (Hasselt: Landelijk Centrum voor Katholieke Actie; Nederlands Pastoraal Instituut; Uitgeverij Heideland)
"redactie Mr. L. C. Baas, Paul Brand jr., Mgr. Mr. A. A. W. Diepenbrock ... et al. Fonds Suzan Daniel (FSD)"